Revisiting Digital Storytelling as a Pedagogical Strategy in Educational Technology: A Systematic Literature Review of Recent Evidence - Pratiwi, Oktovianti; Kustandi, Cecep; Kusumawardani, Dwi; Rahmadi, Imam Fitri (Jurnal Paedagogy, 2026)
This study aims to systematically examine the utilization of digital storytelling (DST) in the context of educational technology, focusing on the digital media used, supporting platforms and their impact on student learning processes and outcomes. The study was conducted using the Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines and involved 36 scientific articles f published in the 2020–2024 period. The results of the thematic analysis showed that the most dominant digital media used was narrative video, followed by digital comics, story-based games and interactive applications. Various platforms and technological tools are utilized, reflecting the flexibility of DST implementation across various educational levels and subject areas. DST implementation has been reported to improve students' learning motivation, emotional engagement, digital literacy, communication and collaboration skills. This study confirms that DST is a technology-based learning strategy that is relevant and adaptive to 21st-century needs. These findings are expected to serve as a reference for developing more effective and contextually grounded digital narrative-based instructional innovations. Future research is recommended to examine how specific types of DST media influence measurable learning outcomes and to develop practical, pedagogically grounded implementation models that can be effectively adopted by teachers across diverse educational contexts.